Respiratory syncytial virus infection in infants and correlation with meteorological factors and air pollutants - Vandini Silvia; Corvaglia Luigi; Alessandroni Rosina; Aquilano Giulia; Marsico Concetta; Spinelli Marica; Lanari Marcello; Faldella Giacomo (BMC, 2013)
Abstract Background Respiratory Syncytial Virus (RSV) is the most important cause of severe respiratory infections in infants with seasonal epidemics. Environmental factors (temperature, humidity, air pollution) could influence RSV epidemics through their effects on virus activity and diffusion. Methods We conducted a retrospective study on a paediatric population who referred to our Paediatric Emergency Unit in order to analyze the correlation between weekly incidence of RSV positive cases during winter season in Bologna and meteorological factors and air pollutants concentration. Results We observed a significant correlation between the incidence of RSV infections and the mean minimum temperature registered during the same week and the previous weeks. The weekly number of RSV positive cases was also correlated to the mean PM10 concentration of the week before. Conclusions RSV epidemic trend in Bologna (Italy) is related to the mean minimum temperature, and the mean PM10 concentration.